THE IMPACT OF SOCIAL MEDIA ON YOUNG PEOPLE’S MINDS - Kuziyeva O.O (TADQIQOTLAR, 2026)
ANNOTATION This article examines how social media influences young people’s thinking, behavior, and emotional well-being. It highlights both positive and negative effects and suggests ways to use social platforms more responsibly.